PENGARUH STRUKTUR MODAL DAN KARAKTERISTIK BANK TERHADAP KINERJA KEUANGAN BANK SYARIAH (Studi Empiris pada Bank Syariah Malaysia Tahun 2012-2014) - Anuttara Eka Dewi Larasati; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2016)
This study discusses about the effect of capital structure and characteristics of the bank on the performance of Islamic banks. This study examined the effect of capital ratio, the ratio of non-earning asset, the ratio of overhead, the ratio of bank size, and the ratio of liabilities on the performance of Islamic banks in Malaysia.The data on this study was obtained from secondary data sources in the form of financial statements and annual reports published through the website of the Central Bank of Malaysia. The sampling technique was taken by purposive sampling. In according the criteria, the samples used amounted to 14 Islamic banks in Malaysia during 2012-2014. The statistical tool used is linear regression analysis with a method: a descriptive statistical analysis, the classic assumption test, and hypothesis testing.The hypothesis testing show that the performance of banks is significantly affected by a capital ratio and the ratio of overhead. Meanwhile, the ratio of non-earning asset, bank size, and the ratio of liabilities does not have a significant effect on performance of banks.